2005
DOI: 10.1159/000084680
|View full text |Cite
|
Sign up to set email alerts
|

Primary Peripheral B Cell Lymphoma, Burkitt-Like, of the Cranial Vault

Abstract: We report an autopsy case of malignant lymphoma of the cranial vault. The patient was an 85-year-old woman who exhibited a painless subcutaneous scalp lump associated with no neurological abnormalities. CT scan and magnetic resonance imaging of the head showed an extra-intra cranial isodensity lesion of the cranial vault. Autopsy revealed that the tumor was composed of medium-sized cells which were immunoreactive with CD45, CD20, CD79a, and CD10, and a diagnosis of peripheral B cell lymphoma, Burkitt-like, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…However, almost any lymphoma histology has been reported causing primary bone disease, including low grade histologies, anaplastic lymphoma [11] and Burkitt lymphoma [12]. Interestingly, the sites of occurrence differ among the various studies: in two series of Japanese patients, PBL most commonly involved the pelvis, [13,14] in others the most common sites of disease were the long bones, [15,16] another study of 131 patients of the British Columbia Cancer Agency reported equal frequency between axial and extremity involvement [17] and finally the SEER database study reported a predominance of axial involvement among 1,500 PBL patients [7], a finding our study shares.…”
Section: Discussionmentioning
confidence: 99%
“…However, almost any lymphoma histology has been reported causing primary bone disease, including low grade histologies, anaplastic lymphoma [11] and Burkitt lymphoma [12]. Interestingly, the sites of occurrence differ among the various studies: in two series of Japanese patients, PBL most commonly involved the pelvis, [13,14] in others the most common sites of disease were the long bones, [15,16] another study of 131 patients of the British Columbia Cancer Agency reported equal frequency between axial and extremity involvement [17] and finally the SEER database study reported a predominance of axial involvement among 1,500 PBL patients [7], a finding our study shares.…”
Section: Discussionmentioning
confidence: 99%
“…This patient had all of these diagnostic criteria. Causes of PLB have been suggested to be inflammation, trauma, or viral infections, but our patient had none of these [3]. …”
Section: Discussionmentioning
confidence: 84%
“…Primary lymphoma of the bone (PLB) is uncommon, accounting for only 7% of all malignant bone tumors and less than 1% of all non-Hodgkin's lymphomas, and the majority of them involve the pelvis or limb bones [1-3]. Primary cranial vault involvement is rarely reported [4].…”
Section: Introductionmentioning
confidence: 99%
“…Our patient was diagnosed at the age of 26, much younger than the median age of this population which was 48 years in 19 similar cases of primary bone lymphoma of the skull which we reviewed [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation was the most commonly seen with skull lymphoma, where most cases reviewed also presented with a scalp lump or swelling [6][7][8][9][10][11][12][13], [15,21,22].…”
Section: Discussionmentioning
confidence: 99%